Sensitivity Analysis of SPR Nanohole Array Structure for Lab-on-Chip Application - Suryanarayana, N. K.; Muniswamy, Venkatesha; Asha, K. (Journal of Optics and Photonics Research, 2025)
In this work, sensitivity analysis of surface plasmon resonance-based nanohole array (SPR NHA) is reported. SPR NHA are suitable for lab-on-a-chip applications. These devices work in three different modes, namely intensity mode, phase mode, and angular mode. In this work, intensity mode analysis is used. The SPR NHA consisting of gold metal and silicon dioxide substrate dielectric material is used. Gold material is widely used in SPR sensors due to its excellent optical properties, high electrical conductivity, and biocompatibility. The finite difference time domain method is used for the simulation and analysis. An optical source at a wavelength of 675 nm is used for the analysis and simulation. The structure of the proposed SPR NHA consists of substrate, which is made of silicon di oxide dielectric material, and a thin layer of gold is deposited on the substrate having thickness 0.1 µm. The NHA is etched on the gold layer. The pitch of the NHA is 0.6 µm and diameter of each hole is 0.2 µm. The diameter of the holes present in NHA is 0.2 µm. The sensitivity of the proposed device for different analytes such as albumin, RBC, and hemoglobin is determined. The maximum sensitivity of 298.35 nm/RIU is achieved for the proposed device. The results obtained show that the sensor has better sensitivity and suitable for use in lab-on-a-chip applications. Received: 23 October 2023 | Revised: 21 December 2023 | Accepted: 21 December 2023 Conflicts of Interest The authors declare that they have no conflicts of interest to this work. Data Availability Statement Data sharing is not applicable to this article as no new data were created or analyzed in this study. Author Contribution Statement N. K. Suryanarayana: Conceptualization, Methodology, Software, Validation, Formal analysis, Investigation, Data curation, Writing – original draft, Writing – review & editing, Visualization, Project administration. Venkatesha Muniswamy: Conceptualization, Validation, Formal analysis, Resources, Data curation, Writing – review & editing, Supervision, Project administration. K. Asha: Conceptualization, Software, Validation, Formal analysis, Resources, Data curation, Writing – review & editing, Visualization, Supervision.